CFD and experimental analysis of a 115 kW natural gas fired lab-scale furnace under oxy-fuel and air–fuel conditions. (1st November 2015) - Mayr, Bernhard; Prieler, Rene; Demuth, Martin; Potesser, Michael; Hochenauer, Christoph
Highlights: CFD modelling of an 115 kW lab-scale furnace. Time saving combustion modelling using the steady flamelet model. Prediction of heat fluxes to a water cooled copper plate in the furnace. Different oxygen enrichments in the oxidizer. Comparison between CFD and measurements. Abstract: This paper investigates a natural gas fired lab-scale furnace with a thermal input between 28 and 115 kW under different O2 /N2 ratios in the oxidizer by computational fluid dynamics (CFD). Results of the simulation were confronted with temperature measurements inside the furnace and heat flux measurements on a water cooled plate inside the furnace. The main goal of this work was to use a detailed chemical mechanism and reduce the calculation time. This was achieved with the steady flamelet (SFM) approach. The advantage of the SFM approach is that the computational chemical calculation can be pre-processed and stored in look up tables. Only two additional equations have to be solved to determine the chemical reaction in the flow field. For the simulation the detailed mechanism skeletal25 was used with 17 species and 25 reactions. Additionally the furnace was simulated with the eddy dissipation concept model (EDC) which other authors mainly use to describe oxy-fuel combustion. For the EDC simulation a refined version of the 4-step mechanism proposed by Jones and Lindstedt was used. The EDC simulation was used as a benchmark to determine the time saving potential of the SFM approach. With the SFM approach the calculation time could be reduced from 4 weeks to 4 days on 8 CPU cores, although a detailed mechanism was being used. The predicted temperatures of the CFD simulations were in good accordance with the measurements and showed the applicability of the skeletal25 mechanism with the SFM approach under different combustion environments. In metal melting or reheating furnace the right prediction of the heat flux on the goods is crucial. Therefore the heat flux on a water cooled plate inside the furnace was determined by measurements and CFD calculations for different combustion environments. For the heat flux at a temperature level of 1070 °C the CFD calculation showed a maximum relative error of 5% to the measurements for 21, 25, 30, 45 and 100 Vol% O2 in the oxidizer. For the temperature level of 1200 °C the maximum error increases, especially for O2 concentration in the oxidizer higher than 45% up to 12%. Both the experiments and the numerical model showed an increase in furnace efficiency with increasing oxygen in the oxidizer. A maximum efficiency of 76% was observed for 100 Vol% in the oxidizer compared to 48% at 21 Vol% O2 . This shows the fuel saving potential of oxygen or oxygen enriched combustion.